The Future of Futurists: Can a Machine Produce This Forecast? - Mayes, Randall (Futurist)
The article discusses the changing trends in the usage of artificial intelligence technique that helps in conducting useful analysis and forecasting using the advances in data and cognitive analytics. Topics discussed include use of reverse engineering method for the simulation of the brain's neural network, use of mind uploading method for the emulation of brain, and use of robot journalism technique and natural language processing.